The interrelationship between medial temporal atrophy and APOE4 biomarker: A comparison between Hispanics and white non‐Hispanics: Developing topics. (7th December 2020) - Garcia, Patricia; Mendoza, Lisandra; Padron, Dileanna; Duarte, Andres; Duara, Ranjan; Loewenstein, David A; Greig‐Custo, Maria T; Barker, Warren W; Rodriguez, Miriam J
Abstract: Background: The Apolipoprotein E (APOE) gene is a major risk factor in developing late‐onset Alzheimer's disease (AD; LOAD; de Oliveira et al., 2017; de Oliveira et al., 2014). The relationships between E4 genotype, brain morphology and ethnicity may provide insights into mechanisms by which ethnicity is associated with risk for AD. Because most research on genetic biomarkers has been conducted with Caucasian samples, this study aimed to explore the relationship of E4 (+) status to regional brain atrophy among an ethnically diverse cohort (Hispanics and White non‐Hispanics [WNH]) that are cognitively normal (CN) or have Mild Cognitive Impairment (MCI). We hypothesized that E4 (+) would be associated with brain atrophy in both ethnic groups. Method: Cross sectional analysis of 240 participants was conducted of which 80 (23.1%) were E4 (+) (mean age= 71.02, SD=7.11); mean education= 14.46 (SD=3.42); 64.9% (n= 48) of the cohort were female. When stratified according to cognitive functioning (CN, MCI), the E4 (+) cohort was comprised of 32 WNHs (46.4%) and 35 Hispanics (50.7%). Pearson correlations were conducted between E4 (+) and volumetric variables (normalized to intracranial volume) in medial temporal regions sensitive to AD pathology—hippocampus, entorhinal cortex (ERC), and parahippocampal cortex (PHC). Result: A significant negative correlation was found between E4 (+) with L‐PHC (r= ‐.352, p= .022) and R‐PHC (r= ‐.348, p=. 024) among the combined CN group. When stratified by ethnicity, a negative correlation was seen in CN‐Hispanics between E4 (+) and L‐PHC (r= ‐.593, p= .002). No significant correlations were identified for WNH in both clinical groups and for MCI‐Hispanics. Conclusion: Our findings indicate that E4 (+) status is associated with medial temporal brain atrophy among cognitively normal individuals. When examining ethnic groups, these correlations were evident among CN‐Hispanics. At the MCI stage, when brain pathology begins, these associations were not as strongly evident. Our findings highlight the importance of studying biomarkers among culturally diverse groups. Given the projected growth of Hispanics in the US, ongoing efforts should aim at disentangling cultural and genetic variables and their contribution to AD pathophysiology.